Development of Green Chemistry-Oriented Student Worksheets for Home Industry Product Manufacturing - Febriana, Baiq Anita (Lembaga Riset Mutiara Akbar, 2025)
This study aims to develop a green chemistry-based Student Worksheet (LKM) that can be used in practical activities for making home industry products, specifically environmentally friendly dishwashing soap. The method used is Research and Development (R&D) with a 4-D development model, which includes the Define, Design, and Develop stages. Validation was carried out by three experts on aspects of content, language, green chemistry principles, and presentation. A limited trial was conducted on 35 students from various study programs. The validation results showed that the LKM was highly valid, with an overall average score of 4.55 on a scale of 5. The practicality of the LKM was also rated very well by students, with an average score of 4.64. This LKM not only helps students understand the principles of green chemistry and carry out contextual practices, but also fosters an entrepreneurial spirit through the creation of environmentally friendly products. The results of the study indicate that the development of a green chemistry-based LKM is effective in improving students' chemical literacy, environmental awareness, and 21st-century skills. Therefore, this LKM is recommended for use in chemistry learning oriented towards sustainability and soft skills development.